Family-based association tests: introduction - Lange, Christoph (Henry Stewart Talks, 2007)
Definition: genetic association, Examples, Linkage disequilibrium, Case-control analysis, Samples from mixed populations, Population admixture, Dichotomous trait, The transmission disequilibrium test (TDT), An alternative formula for the TDT: FBATs, FBATs: no parental genotypes, The general FBAT, FBATs for quantitative traits